INFLUENCE OF THE THINK-PAIR-SHARE (TPS) MODEL AND MOTIVATION ON THE MATH LEARNING ACHIEVEMENT OF CLASS V STUDENTS - Srinarwati Srinarwati (Universitas Trunojoyo Madura, 2022)
The problem is as follows: (1) How is the Think-Pair-Share (TPS) learning model for the learning achievement of Mathematics students in class V? (2) What is the motivation to learn about the learning achievement of Mathematics class V students? (3) Is there a positive interaction of the Think-Pair-Share (TPS) learning model and learning motivation with the math learning achievement of class V students? This study uses explanatory research. Meanwhile, explanatory research is research that highlights the relationship between research variables and tests hypotheses that have been formulated before. The sample taken amounted to 100% of the 4 elementary groups I adjacent considering the distance of the intended school, namely from class V SDN Bluluk I as many as 30, V SDN Talunrejo I as many as 15, V SDN Talunrejo II as many as 19, V SDN Talunrejo III as many as 16, so that the study sample amounted to 80 students. The data analysis technique used in this study is deskritive analysis. In addition to deskritive analysis used double linear regression to know individually then jointly influence the use of the think pair share (TPS) model, learning motivation towards mathematical learning achievement. The results of this study are, (1) The use of the think pair share (TPS) model has a positive, very strong and significant influence on the learning achievement of Mathematics students in class V, (2) Learning Motivation also has a positive, very strong and significant influence on the learning achievement of Mathematics students class V, (3) The use of think pair share (TPS) and Learning Motivation models together has a positive interaction, Very strong and significant to learning achievement.